Phase II basket trial of Dual Anti-CTLA-4 and anti-PD-1 blockade in Rare Tumors (DART) SWOG S1609: pancreatic neuroendocrine neoplasm (PNEN) cohort - Ignacio I Wistuba; Jianhua Zhang; Anup Kasi; Hong Chen; Seunghee Kim-Schulze; Holden T Maecker; Elad Sharon; Razelle Kurzrock; Sacha Gnjatic; Young Kwang Chae; Jiexin Zhang; Jianjun Zhang; et al. (Journal for ImmunoTherapy of Cancer, 2025)
Purpose SWOG S1609 Dual Anti-CTLA-4 and anti-PD-1 blockade in Rare Tumors (DART) studied the efficacy of ipilimumab combined with nivolumab across multiple rare tumor types. We report the results of the pancreatic neuroendocrine neoplasm (PNEN) cohort.Experimental design Treatment consisted of ipilimumab 1 mg/kg intravenously every 6 weeks with nivolumab 240 mg intravenously every 2 weeks. The primary endpoint was overall response rate (ORR) (Response Evaluation Criteria In Solid TumorsRECIST V.1.1). Secondary endpoints include progression-free survival (PFS), overall survival (OS), and toxicity. Clinical benefit rate (includes ORR plus stable disease (SD)>6 months was examined. Correlative studies were performed. The trial was conducted by the National Cancer Institute/Southwest Oncology Group Early Therapeutics and Rare Cancers Committee and opened at >1,000 sites.Results 19 patients with PNEN were enrolled. The median number of lines of prior therapy was 2 (range: 0–4). The ORR was 11% (2/19 patients); the clinical benefit rate (CBR; stable disease >6 months+partial response+complete response), 26% (5/19). The median PFS was 3 months; median OS, 24 months. The longest PFSs were 26 (intermediate grade PNEN), 31 (low grade) and 39+months (intermediate grade). The most common toxicities were fatigue (47% of patients) and aspartate aminotransferase (AST) elevation (32%); the most common grade 3/4 immune-related adverse event (AE) was AST (32%) and bilirubin elevation (26%), with no grade 5 events. Programmed death-ligand 1 expression by chromogenic immunohistochemistry (N=12 patients assessed) did not associate with ORR; tumor mutation burden (TMB) was high in three patients; one of the two patients with partial remission (PFS=26 months) had high TMB (150 mutations/mb). Peripheral effector memory T-cell activation (N=11 patients assessed by cytometry by time-of-flight with 5 having longitudinal analysis) was associated with response, though the number of patients evaluated was limited.Conclusions Low-dose ipilimumab plus nivolumab demonstrated an 11% ORR and 26% CBR (includes SD>6 months) in patients with refractory PNEN, with durable benefit (>2 years) in 3 (16%) patients.Trial registration number NCT02834013.